Targeted in vitro gene silencing of E2 and nsP1 genes of chikungunya virus by biocompatible zeolitic imidazolate framework - Tagore, Rajarshee; Alagarasu, Kalichamy; Patil, Poonam; Pyreddy, Suneela; Polash, Shakil Ahmed; Kakade, Mahadeo; Shukla, Ravi; Parashar, Deepti (Frontiers in Bioengineering and Biotechnology, 2022)
Chikungunya fever caused by the mosquito transmitted Chikungunya virus (CHIKV) is a major public health concern in sub-tropical and temperate climatic regions. The lack of any licensed vaccine or antiviral agents against CHIKV warrants development of effective antiviral therapies. Earlier, we have reported that siRNAs targeted against nsP1 and E2 genes lead to inhibition of CHIKV replication in CHIKV infected cells and mice models. The therapeutic efficiency of siRNA can be improved by using an efficient delivery system. Recent studies have indicated that metal organic framework (MOF) biocomposites can protect and efficiently deliver nucleic acids into cells. In the present study, ZIF-C (a polymorph of zeolitic imidazolate framework- 8, ZIF-8) biocomposites have been utilized to deliver siRNAs targeted against E2 and nsP1 genes of CHIKV to achieve a reduction in viral replication and infectivity. Cellular transfection studies of E2 and nsP1 genes targeting free siRNAs and ZIF-C encapsulated siRNAs in CHIKV infected Vero CCL-81 cells were performed. Our results reveal a significant reduction of infectious virus titre, viral RNA levels and percent of infected cells in cultures transfected with ZIF-C encapsulated siRNA compared to cells transfected with free siRNA. The results suggest that delivery of siRNA through ZIF-C enhances the antiviral activity of CHIKV E2 and nsP1 genes directed siRNAs.